Conceptual design of a new two-seater hoverwing craft - Pua’at, Afifi A.; Zhahir, Amzari; Ahmad, Mohamed Tarmizi; Hassan, Aziz; Abdul Hamid, Mohd Faisal; Gires, Ezanee (The Aeronautical and Astronautical Society of the Republic of China, 2025)
This paper presents the conceptual design of a new two-seater Hoverwing, a Wing-in-Ground (WIG) craft, developed to advance the capabilities of ground-effect vehicles. The design process adheres to a structured systems engineering approach, utilizing tools such as Affinity Diagrams, Tree Diagrams, FAST Diagrams, and Quality Function Deployment (QFD) to guide development. A Morphological Matrix generated six potential design solutions, refined through Pugh Matrix analysis, with the final design chosen for its optimal aerodynamic performance, especially minimal center of pressure (COP) migration, determined through XFLR5 software simulations. The Hoverwing's mission profile includes personal recreation, coastal transport, and pilot training, offering a versatile platform for various applications. Key specifications include a weight range of 500-600kg, operating speeds between 120-150km/h, a range of 250-300km, and an endurance of 3-4 hours. This design ensures stable and efficient flight in ground effect zones while providing necessary control and stability for pilot training. The final design meets criteria for safety, performance, and fuel efficiency, marking a significant advancement in small-scale WIG craft.